2018
DOI: 10.1093/carcin/bgy150
|View full text |Cite
|
Sign up to set email alerts
|

18β-glycyrrhetinic acid inhibited mitochondrial energy metabolism and gastric carcinogenesis through methylation-regulated TLR2 signaling pathway

Abstract: The natural phenolic substance, 18β-glycyrrhetinic acid (GRA), has shown enormous potential in the chemoprevention of cancers with rich resources and biological safety, but the GRA-regulated genetic and epigenetic profiles are unclear. Deregulated mitochondrial cellular energetics supporting higher adenosine triphosphate provisions relative to the uncontrolled proliferation of cancer cells is a cancer hallmark. The Toll-like receptor 2 (TLR2) signaling pathway has emerged as a key molecular component in gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Semaphorins and their receptors are significant axon guidance factors that participate in tumor cell migration [ 39 ]. The Toll-like receptor signaling pathway is critical for gastric cancer cell migration and proliferation [ 40 , 41 ]. The Notch signaling pathway is a crucial pathway in the occurrence and development of tumor [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semaphorins and their receptors are significant axon guidance factors that participate in tumor cell migration [ 39 ]. The Toll-like receptor signaling pathway is critical for gastric cancer cell migration and proliferation [ 40 , 41 ]. The Notch signaling pathway is a crucial pathway in the occurrence and development of tumor [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…18β-Glycyrrhetinic acid (GA) is released from glycyrrhizin through hydrolysis. It is extracted from the roots of licorice, and exhibits various anti-inflammatory [1][2][3][4][5], antioxidation [6][7][8][9], and antimicrobial activities [10]. GA is used widely in the pharmaceutical industry [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DHX9 plays an important role in promoting the metastasis of colorectal cancer (Hou et al, 2021). TLR2 belongs to the Toll-like receptor family and is a key regulator of innate and acquired immune responses (Cao et al, 2019). We found that dendritic cells, macrophages, and neutrophils infiltration into CG tumors were positively correlated with the risk score.…”
Section: Discussionmentioning
confidence: 77%